2013
DOI: 10.1089/g4h.2013.0048
|View full text |Cite
|
Sign up to set email alerts
|

Developing Games for Health Behavior Change: Getting Started

Abstract: Many investigators are considering developing videogames for health (video-G4Hs) but have questions about how to get started. This report provides guidance for investigators considering a G4H as a behavioral intervention procedure from a team of experienced G4H developers. Thirteen commonly asked questions are answered, including defining a G4H, considerations in developing a team, considerations in G4H design, and anticipating unintended consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 60 publications
0
107
0
3
Order By: Relevance
“…38,39 Using health behavior theory to guide intervention design may thus increase intervention effectiveness. 40 Indeed, in our review, the theory-based ''American Horsepower Challenge'' 32 showed a significant increase in physical activity compared with baseline, although with a small effect size. Achterkamp et al, 41 who analyzed data from participants who used an ambulant activity coach in daily life, suggested that especially self-efficacy and stage of change (part of the Transtheoretical Model) are two aspects from behavioral change theories that appear important when developing technology-supported physical activity interventions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…38,39 Using health behavior theory to guide intervention design may thus increase intervention effectiveness. 40 Indeed, in our review, the theory-based ''American Horsepower Challenge'' 32 showed a significant increase in physical activity compared with baseline, although with a small effect size. Achterkamp et al, 41 who analyzed data from participants who used an ambulant activity coach in daily life, suggested that especially self-efficacy and stage of change (part of the Transtheoretical Model) are two aspects from behavioral change theories that appear important when developing technology-supported physical activity interventions.…”
Section: Discussionmentioning
confidence: 68%
“…42 Goal setting enables the player to extrapolate what is learned in the game to his or her own real life. 40 Rodr铆guez et al 29 incorporated historical information and reflection, to help the user to remain focused on the commitment to change by making him or her aware of past behavior as it relates to set goals. This largely resembles the Goal Setting Theory, in which goals have been shown to be most effective when they are important to the individual, realistic, shown in relation to the user's progress, and combined with positive feedback as progress toward the goal is made.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A multidisciplinary team was involved in the development of the game, focusing on the entertaining nature of the game (''funness'' members) and content validity (''serious-ness'' members). 24,25 The team included five game developers and two game designers, a physician specializing in mental health and disorders, two academics specializing in behavioral change and serious games, and several older adults as game testers.…”
Section: Game Development Processmentioning
confidence: 99%
“…The following are game elements established in both literature and practice for impacting health behavior [45][46][47][48][49]:…”
Section: Gamification and Game Elementsmentioning
confidence: 99%